The effect of using visual mnemonics on long-term memory retention for History subject - Khairuddin, Nurul Syadiyah; Mailok, Ramlah; Azizan, Ummu Husna (Journal of ICT in Education, 2025)
The challenge of history is the method of teaching and learning, and the prevalence of teachers using lectures or various lecture methods. Developing student ability mastery in this subject is one of the major challenges faced by the teachers. Therefore, this study aims to examine the effect of visual mnemonic developed based on imagery techniques that is the integration of keywords with images or objects on the retention of long-term memory for the subject of History form one. The study was conducted experimentally with one group. A total of 24 students were involved in this study. A pre-posttest was performed for comparison and the next test was a comparison of three different time intervals over a period of weeks. Data were analyzed using a t-test and ANOVA Test. The results showed that there was a significant difference in scores between pre and post-tests. However, the retention test showed no significant difference in score for the three different times. Visual mnemonics show a good effect on long-term memory. The results of this study can be used as a method of teaching and learning, especially for factual subjects.